2011
DOI: 10.1007/s00249-011-0767-3
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic levitation: recent developments and emerging opportunities in biomaterials research

Abstract: Containerless sample environments (levitation) are useful for study of nucleation, supercooling, and vitrification and for synthesis of new materials, often with non-equilibrium structures. Elimination of extrinsic nucleation by container walls extends access to supercooled and supersaturated liquids under high-purity conditions. Acoustic levitation is well suited to the study of liquids including aqueous solutions, organics, soft materials, polymers, and pharmaceuticals at around room temperature. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Over the past decades, this method has also been proven to be very robust for various other systems, including jets (Ronay 1978a, b), bubbles (Leighton 1994;Brennen 1995), liquid samples of blood and biological tissues (Weiser and Apfel 1982;Weber et al 2012) and soap bubbles (Kornek et al 2010;Grinfeld 2012). The very early work of Rayleigh (1879) and Lamb (1881) showed that a liquid that is deformed from its equilibrium state can be treated as an oscillator (system), where surface tension provides the restoring force.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, this method has also been proven to be very robust for various other systems, including jets (Ronay 1978a, b), bubbles (Leighton 1994;Brennen 1995), liquid samples of blood and biological tissues (Weiser and Apfel 1982;Weber et al 2012) and soap bubbles (Kornek et al 2010;Grinfeld 2012). The very early work of Rayleigh (1879) and Lamb (1881) showed that a liquid that is deformed from its equilibrium state can be treated as an oscillator (system), where surface tension provides the restoring force.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, new levitation techniques have been proposed to manipulate and to transport small samples of solids and liquids. [23][24][25][26][27][28] These new techniques offer many possibilities in the areas of biology, 29 chemistry, 30 pharmacy, 6,31 and in the handling of microelectronic components. 32,33 A possible application is to replace the conveyor belts of modern industries for new types of transportation systems that can transport micro components and substances without contact.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic levitation [1,2,3] has been developing from the 70-90's as a contactless technology in chemical and pharmaceutical industry [4,5] of ultra-pure materials. The technology facilitates preventing the liquid contamination and intensifying the chemical reactions.…”
Section: Introductionmentioning
confidence: 99%